Eco-Tethered Liberation: A New Spirituality for the Anthropocene - Appolloni, Simon (The Trumpeter, 2018)
To counter the Anthropocene epoch marked by complex webs of exploitation, this paper elucidates an ethics of liberation that applies to all of creation replete with its concomitant relational complexities, which the author calls eco-tethered liberation. The paper delineates how we can both understand and actualize the liberation of the whole of creation, which is an invariably messy communal process of dialoguing and negotiating with many others. This paper further explores the concept of sumaq kawsay as an example of eco-tethered liberation being lived out by the largely Indigenous Bolivian population today. The paper culminates in suggesting that this new ethic of liberation for the Anthropocene is itself a new spirituality for the Anthropocene.